Carapanãs (Diptera: Culicidae) antropofílicos da zona urbana da cidade de Belém, Pará, Brasil - Vieira, Paoola Cristina Bezerra (Museu Paraense Emílio Goeldi, 2023)
This behavior is related to the need of the females for proteins from the blood of vertebrate animals, to enable their reproductive processes and maturation of eggs. Carapanans are diptera of the suborder Nematocera, family Culicidae, which is subdivided into two subfamilies: Anophelinae and Culicinae, the latter containing the largest number of species. They are insects of great epidemiological importance, since they are involved in the transmission of diseases such as malaria, filariasis and several arboviruses to humans. This work aims to study the anthropophilic Culicídae species in the urban area of the city of Belém in different areas. The collections were performed in three different areas of the city: downtown, peri-center and periphery. Every two months, CDC traps were installed in the peridomicile of each mentioned area, in the interval from 6:00 PM to 7:00 AM the next day. Collections with human bait were made in the peridomestic and domicile of the residences located in the mentioned points, from 6:00 PM to 9:00 PM. Five collections were performed in August, October and December 2003, February and April 2004. A total of 530 mosquitoes were captured, 491 of Culex, 36 of Aedes and 3 of Anopheles. 470 specimens were captured with human bait and 60 in CDC traps. Specimens of the Psychodidae family and other diptera were also captured in CDC. As for the collection points, 244 mosquitoes were captured in the central area of Belém, 203 in the peri-central area and 83 in the periphery. The results, although preliminary, indicate higher density in the central, peri-central and peripheral areas, respectively, as expected, considering previous collections. The number of specimens collected increased considerably perhaps due to the rainfall index of 2004 which was higher than that of 2003 and the greater experience of the collectors.